Silk fibroin-based hydrogels and scaffolds for osteochondral repair and regeneration - Ribeiro, Viviana Pinto (2018)
Osteochondral lesions treatment and regeneration demands biomimetic strategies aiming physicochemical and biological properties of both bone and cartilage tissues, with long-term clinical outcomes. Hydrogels and scaffolds, appeared as assertive approaches to guide the development and structure of the new osteochondral engineered tissue. Moreover, these structuresalone or in combination with cells and bioactive molecules, bring the mechanical support after in vitro and in vivo implantation. Moreover, multilayered structures designed with continuous interfaces, furnish appropriate features of the cartilage and subchondral regions, namely microstructure, composition, and mechanical properties. Owing the potential as scaffolding materials, natural and synthetic polymers, bioceramics, and composites, have been employed. Particularly, significance is attributed to the natural-based biopolymer silk ï¬ broin from the Bombyx mori silkworm, considering its unique mechanical and biological properties. The significant studies on silk fibroin-based structures, namely hydrogels and scaffolds, towards bone, cartilage, and osteochondral tissue repair and regeneration are overviewed herein. The developed biomimetic strategies, processing methodologies, and final properties of the structures are summarized and discussed in depth.